Implementation of the Healthy School Program in Junior High School - Rr Mini Sariwulan (AL-ISHLAH: Jurnal Pendidikan, 2023)
A healthy school is a school that has a living environment that reflects a healthy life, so as to ensure that the learning process takes place properly and creates conditions that support the achievement of students' ability to live a healthy life. This study aims to determine how to implement a healthy school program in a junior high school in Unggul Sekayu.  Informants in this study were seven people consisting of school principals, teachers, employees, and students. Data was collected through observation, interviews and documentation. Meanwhile, data analysis uses data reduction, presentation, and conclusion drawing. This research shows that the healthy school program at junior high school in Unggul Sekayu runs according to the SKB 4 Ministerial regulations and has a vision, mission, benefits, goals, and opportunities. The healthy school program is supported by human resources such as principals and vice principals, students, teachers, staff, P2M, UKS team, infrastructure and curriculum. In the process, it uses the "Rekayasa" strategy (plan, do and get used to), which is supported by adequate infrastructure, UKS activities, KKR/PMR, activities for the formation of physical and spiritual health, and partnerships. The implementation of the healthy school program succeeded in turning the junior high school into an Environmentally Friendly School (Adiwiyata) and a Healthy School at the National Level. This research implies that the healthy school program needs to be a model for other schools, which can have an impact on healthy and clean living behaviour in students.